Association of genotypes at the matrix metalloproteinase (MMP) loci with carotid IMT and presence of carotid and femoral atherosclerotic plaques - Panayiotou, Andrie G.; Griffin, Maura B.; Tyllis, Theodosis H.; Georgiou, Niki; Bond, Dawn; Humphries, Steve Eric; Nicolaides, Andrew N. (My University, 2013)
We aimed to test the association between matrix metalloproteinase (MMP) genetic polymorphisms and (a) intima-media thickness in the common carotid (IMTcc) and (b) the presence of plaques in the carotid and femoral bifurcations. Carotid and femoral bifurcations were scanned with ultrasound in 762 Cypriot community dwellers (46% men) over the age of 40 years. IMTcc and the presence of plaques were recorded. The MMP1 1G/2G, MMP3 5A/6A, MMP7 -181A>G, MMP9 R279Q, and MMP12 -82A>G polymorphisms were determined with the TaqMan method. In men, the presence of plaques in any bifurcation was associated with the MMP9 279Q allele (ORadjusted=4.50; 95% CI=2.0 to 10.1; p<0.001) and the MMP7 -181A allele was associated with the presence of femoral plaques (ORadjusted=2.61; 95% CI=1.36 to 4.99; p=0.004). In women, the presence of femoral plaques was associated with the MMP12 -82G allele (ORadjusted=1.9; 95% CI=1.14 to 3.16; p=0.014). Our results suggest that the effect of common MMP genotypes on plaque presence may be site- and sex-dependent.
Keywords: Atherosclerosis; Carotid plaques; Femoral plaques; Genetic polymorphisms; Intima-media thickness (IMT); Matrix metalloproteinases (MMP)